Regularity of Global Attractor for the Reaction-Diffusion Equation - Hong Luo (Abstract and Applied Analysis)
By using an iteration procedure, regularity estimates for the linear semigroups, and a classical existence theorem of global attractor, we prove that the reaction-diffusion equation possesses a global attractor in Sobolev space Hk for all k>0, which attracts any bounded subset of Hk(Ω) in the Hk-norm.